Penegakan Hukum Terhadap Pelaku Tindak Pidana Pengancaman Kekerasan dan Pembunuhan Melalui Media Sosial - Putu Diah Premana Putri; I Nyoman Gede Sugiartha; Diah Gayatri Sudibya (Jurnal Preferensi Hukum, 2022)
Advances in technology are increasingly taking over space in the field of human life to facilitate human activities. With the many facilities offered, it is easier for humans to do things that are not in accordance with what should be done, such as committing crimes of threats of violence and murder through social media that are rife in today's society. With this phenomenon, the Indonesian government has issued several rules for law enforcement against perpetrators of criminal acts of threats of violence and murder through social media as regulated in Article 335 paragraph (1) 369 paragraph (1) of the Criminal Code and Article 45B of the ITE Law. Therefore, this study examines the causes of criminal acts of threats of violence and murder through social media and examines law enforcement against perpetrators of criminal acts of threats of violence and murder through social media. This study uses a normative legal research type with a statutory approach. The material used is primary legal material, which is the main legal material that is the basis for reviewing the problems under study, then supported by secondary materials. To obtain valid data, researchers used library research techniques. Furthermore, the research data is processed and analyzed by means of legal interpretation based on deductive and inductive logic. The results showed that the cause of the perpetrators committing the crime was due to internal factors, namely uncontrolled psychology and emotions and economic factors. Then regarding the sanctions that will be imposed on the perpetrators in accordance with the Criminal Code and the ITE Law which will be decided in the trial process.